Optimization of the Differential Pulse Cathodic Stripping Voltammetry Technique for the Determination of Nickel in Pengkalan Chepa River, Kelantan - Azlina, Mat Shariff (Universiti Sains Malaysia, 2009)
Nickel is a very toxic heavy metal which is significant subject of environmental surveillance, food control and occupational medicine, toxicology and hygiene. Various techniques have been used for the determination of this heavy metal including inductively"coupled plasma mass spectrometry (ICP"MS}, flame atomic absorption spectrometry (F AAS) and atomic emission spectrometry (AES). However, these methods are having disadvantages particularly time consuming in sample preparation. A voltammetric method as an alternative method for the determination of the nickel in the river water samples of Pengkalan Chepa River is described. In this study the determination of nickel in the river water samples collected from Pengkalan Chepa River was performed by using Differential Pulse Cathodic Stripping Voltammetry (DPCSV) analysis. All samples were collected from Pengkalan Chepa River at various places including those from surface and the bottom of the river. From the study, the optimum condition for the supporting electrolyte, Britton-Robinson Buffer (BRB), 0.04 M was determined to be at pH 4. The optimum voltammetric parameters with initial potential, Ei was -0.70 V, fmal potential, Er was "1.15 V, scan rate, v was 0.020 V/s, deposition potential, Eacc was -0.70 V, deposition time, tacc was 0 second and equilibrium time, teq was 10 seconds. The calibration curve was constructed, using peak height, Ip versus concentration of nickel standard solution (5 ppm). A linear graph with regression equation, Y= 20.131X + 0.743 and correlation coefficient, r was 0.999. Standard deviation (SD) was 1.063, sensitivity 20.131 nA/ppm and limit of detection was 0.158 ppm or 158 ppb. The results from this study show that nickel was not detected in all samples using our experimental conditions.